Fungsi Kepemimpinan dan Manajemen Kepala Ruang Berbasis Bureaucratic Caring Theory terhadap Pelayanan Keperawatan - Leon, Yulius Mau; Dedi, Blasius; Kusumaningsih, Indriati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the functions of leadership and management functions of the head of the room based on bureaucratic caring theory towards nursing services at X Pontianak Hospital. The research method used was qualitative with an exploratory phenomenology approach. approach. The results of this study resulted in 15 themes, namely the time line time line is the foundation in carrying out an effective management planning function, the importance of the head of the room's planning activities in managing facilities, the flow of planning coordination flow, conformity with planning in Hospital X Hospital X Pontianak, supervision to improve performance and professional development of nursing, nursing methods used in the hospital, nursing methods used in the hospital, and nursing methods used in the hospital. methods used in the hospital, chain of command system as a workflow in the organization, mentor for workflow in the organization, mentors for nurses in the hospital, rewards for nurses in the hospital, overcoming conflicts as soon as possible. nurses in the hospital, resolving conflicts as soon as possible to avoid further problems, delegation of tasks according to further problems, delegation of tasks according to the direction of the head of the unit, supervision related to documentation, performance appraisal of nurses using DP3, the process of controlling the process of controlling nursing services to improve service quality, the hope of the head of the room to the leader or direct supervisor so that his role is optimal. The conclusion that can be drawn from this research is that the head of the room needs to develop leadership and management functions head of the room based on Bureaucratic Caring Theory on nursing services. nursing services. Keywords: Leadership, Department Head Management, Management, Bureaucratic Caring, Phenomenology